Visual impairment and progressive phthisis bulbi caused by recessive pathogenic variant in MARK3. (16th May 2018) - Ansar, Muhammad; Chung, Hyunglok; Waryah, Yar M; Makrythanasis, Periklis; Falconnet, Emilie; Rao, Ali Raza; Guipponi, Michel; Narsani, Ashok K; Fingerhut, Ralph; Santoni, Federico A; Ranza, Emmanuelle; Waryah, Ali M; et al.
Abstract: Developmental eye defects often severely reduce vision. Despite extensive efforts, for a substantial fraction of these cases the molecular causes are unknown. Recessive eye disorders are frequent in consanguineous populations and such large families with multiple affected individuals provide an opportunity to identify recessive causative genes. We studied a Pakistani consanguineous family with three affected individuals with congenital vision loss and progressive eye degeneration. The family was analyzed by exome sequencing of one affected individual and genotyping of all family members. We have identified a non-synonymous homozygous variant (NM_001128918.2: c.1708C > G: p.Arg570Gly) in the MARK3 gene as the likely cause of the phenotype. Given that MARK3 is highly conserved in flies (I: 55%; S: 67%) we knocked down the MARK3 homologue, par-1, in the eye during development. This leads to a significant reduction in eye size, a severe loss of photoreceptors and loss of vision based on electroretinogram (ERG) recordings. Expression of the par-1 p.Arg792Gly mutation (equivalent to the MARK3 variant found in patients) in developing fly eyes also induces loss of eye tissue and reduces the ERG signals. The data in flies and human indicate that the MARK3 variant corresponds to a loss of function. We conclude that the identified mutation in MARK3 establishes a new gene-disease link, since it likely causes structural abnormalities during eye development and visual impairment in humans, and that the function of MARK3 / par-1 is evolutionarily conserved in eye development.